2006
DOI: 10.1002/ppul.20396
|View full text |Cite
|
Sign up to set email alerts
|

Are lower airway or throat cultures predictive of sinus bacteriology in cystic fibrosis?

Abstract: The choice of antibiotics for sinusitis in children with cystic fibrosis (CF) is empirical or based on lower airway cultures, because sinus cultures are difficult to obtain. The aim of this study was to identify the main organisms cultured from CF children with chronic sinusitis, and to evaluate the concordance of concomitant sinus, oropharyngeal swab (OP), and bronchoalveolar lavage fluid (BALF) cultures. OP and BALF cultures were done preoperatively, and sinus cultures were obtained during clinically indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
72
1
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 32 publications
11
72
1
9
Order By: Relevance
“…In a large cohort study, almost half of the patients with a history of chronic P. aeruginosa lung infection also had an infection with the same genotype in the upper airways (Mainz et al, 2009). Identical genotypes in the sinus and bronchoalveolar lavage (lung) samples have also been recovered from one study of CF children with chronic sinusitis, and the frequency of identical genotypes increased from 9% of children up to 8 years old to 30% of children more than 8 years old (Muhlebach et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a large cohort study, almost half of the patients with a history of chronic P. aeruginosa lung infection also had an infection with the same genotype in the upper airways (Mainz et al, 2009). Identical genotypes in the sinus and bronchoalveolar lavage (lung) samples have also been recovered from one study of CF children with chronic sinusitis, and the frequency of identical genotypes increased from 9% of children up to 8 years old to 30% of children more than 8 years old (Muhlebach et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the second-site colonization events in the sinuses, often being more persistent than those in the lungs, may provide extended opportunities for evolution of the bacteria towards phenotypes, with greatly increased potential of creating chronic lung infections as well. Although it has long been known that the microbiotas of the upper and lower airways are similar in chronically infected CF patients, only a small number of studies have investigated the possibility of cross-infections between the paranasal sinuses and the lungs (Dosanjh et al, 2000;Muhlebach et al, 2006;Mainz et al, 2009). In a large cohort study, almost half of the patients with a history of chronic P. aeruginosa lung infection also had an infection with the same genotype in the upper airways (Mainz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[49][50][51][52] Muhlebach et al 53 studied lower airway and throat cultures and reported that P. aeruginosa as well S. aureus are the most common bacterial species found in CF patients. There is a higher frequency of Pseudomonas colonization in the lower airways in patients who have CRS with NPs and is more likely to start in the sinuses at a younger age and progress to involve both the upper and the lower airways.…”
Section: Microbiologymentioning
confidence: 99%